THE ROLE OF ISLAMIC SOCIAL FINANCE IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Rakhmi Adrianti Hapsari (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2026)
Islamic Social Finance (ISF) has emerged as a strategic instrument for supporting the achievement of the Sustainable Development Goals (SDGs) through its contributions to poverty alleviation, human capital development, inclusive economic growth, and inequality reduction. This study aims to analyze the role of Islamic social finance in achieving sustainable development. Using a qualitative approach and a systematic literature review (SLR) method, this research examines approximately 30 scholarly articles and institutional reports related to zakat, waqf, sadaqah, infaq, Islamic microfinance, and SDGs. The findings reveal that Islamic social finance significantly contributes to SDG 1 (No Poverty), SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities). Furthermore, the integration of governance, institutional collaboration, and digital innovation enhances the effectiveness of Islamic social finance programs. This study concludes that Islamic social finance represents a comprehensive and sustainable development framework capable of promoting inclusive growth, social welfare, and equitable development while supporting the broader achievement of the SDGs.